(untitled) (Physical Culture and Sport: Scientific Perspective, 2022)
The modern world is a continuous flow of information. And, often, it is very difficult to distinguish the rational grain in it. It’s no secret that students’ visual attention is one of the most practical, because listening rarely reaches 50 per cent of the information. Students do not hear themselves, do not hear the interlocutor, do not perceive information by ear. This limits the ability to perceive and process information and the ability to navigate the information space. It is the role of the teacher to use and create learning materials that will ensure the comprehensive development of students and their critical thinking. Innovative pedagogical technologies are one of the best ways to present knowledge and organise information using images. The technology of developing critical thinking is becoming increasingly popular in modern education. And this is where innovative technologies have found their full application. Thanks to them, the hidden process of thinking becomes visible, acquires a visual embodiment, because the use of innovative technologies promotes the development of critical thinking and allows you to deploy thought processes on the plane. But before choosing a particular teaching method for the lesson, the teacher must answer the following questions: how he or she feels about the content, what are the central facts, ideas, arguments, processes that students need to understand; what scheme will best organise the material and fill it with meaning; what type of innovative technology will help students analyse and comprehend the content; what questions need to be asked, how to organise the actualisation of subjective experience on the topic to activate students’ thinking. That is, the teacher needs to be aware of why he or she chooses a particular method of work and what goal he or she can achieve with it. If you follow all the tips, carefully select the educational material and take a responsible attitude to the choice and method of innovative pedagogical technologies, this will definitely allow students to memorise the necessary amount of information (most importantly on the topic) and help them retrieve it from memory much faster and reproduce it at the right time.